HUBUNGAN RIWAYAT IBU HAMIL KEKURANGAN ENERGI KRONIK (KEK) DENGAN DERAJAT STUNTING PADA ANAK DI DESA MEKAR SARI LOMBOK TIMUR - Baiq Dwi Sagita Alawiah; Dewi Utary; Aulia Mahdaniyati; Adib Shammakh (Nusantara Hasana Journal, 2023)
Stunting is one of the malnutrition conditions associated with past nutritional insufficiency that it is included in chronic nutritional problems. In 2021 East Lombok will have a proportion of stunted toddlers of 18.1% with a total of 22,080 toddlers, but there has been an increase in the proportion of stunted toddlers from 2020 with a total of 16,058 toddlers. Research purposes, to find out the mother's history of chronic energy deficiency (CED) with the degree of stunting in children in Mekar Sari Village, East Lombok. This research is an observational analytic study with a cross sectional design. The sample in this study was stunting toddlers in Mekar Sari village, East Lombok. A sample of 64 respondents was taken using the total sampling method. The research data were analyzed using the Chi Square test. The results of the Chi Square test analysis show p-value 0.033 (P-value ≤ 0.05) which means there is a significant relationship between the history of pregnant women and the degree of stunting in children in Mekar Sari Village, East Lombok. There is a relationship between the mother's history of chronic energy deficiency (KEK) and the degree of stunting in children in Mekar Sari Village, East Lombok.